2022
DOI: 10.3390/bioengineering9120809
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for 3D Spinal Posture Based on Videorasterstereographic Analyses of Healthy Adults

Abstract: Visual examinations are commonly used to analyze spinal posture. Even though they are simple and fast, their interrater reliability is poor. Suitable alternatives should be objective, non-invasive, valid and reliable. Videorasterstereography (VRS) is a corresponding method that is increasingly becoming established. However, there is a lack of reference data based on adequate numbers of participants and structured subgroup analyses according to sex and age. We used VRS to capture the spinal posture of 201 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…All subjects showed an apical deviation and surface rotation to the right, which increased with increasing walking speed, which is in agreement with two previous publications for reasons that are still unknown [[ 29 , 43 ]]. Possible explanations have been discussed, with most people being right-handed or, alternatively, the left anterolateral pulsatile force of the thoracic aorta causing an asymmetric effect with surface rotation to the right [[ 44 ]].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All subjects showed an apical deviation and surface rotation to the right, which increased with increasing walking speed, which is in agreement with two previous publications for reasons that are still unknown [[ 29 , 43 ]]. Possible explanations have been discussed, with most people being right-handed or, alternatively, the left anterolateral pulsatile force of the thoracic aorta causing an asymmetric effect with surface rotation to the right [[ 44 ]].…”
Section: Discussionsupporting
confidence: 92%
“…Schroeder et al [ [ 27 ]], however, only used static spinometry measuring people aged 25.4 ± 5.5 years with similar anthropometrics, but the number of subjects was limited to 20 (9 females, 11 males). Probably the most comprehensive spinometric data collected and published by the working group surrounding Huthwelker et al [[ 43 ]] and Wolf et al [ [ 50 ]] have not yet published dynamic data. Only Michalik et al [ [ 29 ]] dynamically measured 121 subjects (56 females, 65 males; age 24.1 ± 2.16 years) to investigate gender differences in spinal posture between static and dynamic spinometry.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding global motion analyses, validated multibody models have been used to quantify postures in healthy adults, gait initiation in patients with Parkinson’s disease, walking patterns in pregnant women, running performance, and swimming performance. Huthwelker et al [ 6 ] quantitatively measured the spine postures in healthy adults of different age and gender groups, serving as reference data for studies of abnormal spine postures. The freezing of gait is common in patients with Parkinson’s disease and may lead to falls; thus, Palmisano et al [ 7 ] investigated underlying balance control in gait initiation and identified that the center of pressure parameters, rather than the center of mass parameters, could be related to the freezing of gait.…”
Section: Evaluation Of Motion Patterns Using Validated Biomechanical ...mentioning
confidence: 99%
“…Preventive examinations are important in promoting public health. One possibility for doing so is the examination of posture parameters [16][17][18]. The classification of normal and abnormal posture is often based on subjective empirical values [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to manual 2D photograph analysis, stereophotogrammetric systems scan the back contour without contact or radiation exposure using light grids and record their spatial shape with high accuracy [22][23][24]. Ohlendorf [19,[25][26][27], Ludwig [17], and Wolf and Huthwelker [16,28] defined reference values for certain target groups using 3D stereophotogrammetry, which can be used to preventively assess spine posture and reflecting the expected standard values for healthy individuals.…”
Section: Introductionmentioning
confidence: 99%